2010
DOI: 10.1111/j.1440-1819.2010.02093.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between alexithymia and pain severity, depression, and anxiety among patients with chronic and episodic migraine

Abstract: Aims: Some studies have found elevated alexithymia among patients with chronic pain, but the correlations between alexithymia and the severity of pain, depression, and anxiety among migraine patients are unclear. The aims of the present study were to investigate whether individuals suffering from episodic migraine (EM) differ from those with chronic migraine (CM) in regards to depression, anxiety, and alexithymia measures and to investigate the association of alexithymia with the results of depression and anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 42 publications
2
20
0
8
Order By: Relevance
“…There is a well established relationship between migraine, depression and anxiety [9,28]. Accordingly, in our study population depression was correlated with all the domains of sexual function.…”
Section: Discussionmentioning
confidence: 65%
“…There is a well established relationship between migraine, depression and anxiety [9,28]. Accordingly, in our study population depression was correlated with all the domains of sexual function.…”
Section: Discussionmentioning
confidence: 65%
“…Such a transition may determine increased disability [3] and may be accompanied by decreased mood state [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that patients with CM-MO display higher disability and lower mood compared to EM[3,4], but mood state has never been connected to disability, measured with a multi-domain assessment tool like the WHO-DAS-2.…”
mentioning
confidence: 99%
“…They found that compared to healthy controls, the subjects with headaches had significantly higher scores on measures of depression and alexithymia. However, to date, a clear correlation between alexithymia and pain has not been established (8).…”
Section: The Etiology Of Alexithymiamentioning
confidence: 99%